1977
DOI: 10.1021/jm00219a001
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral dopamine agonist properties of some 2-aminotetralin derivatives after peripheral and intracerebral administration

Abstract: A series of variously N-substituted 2-aminotetralins having OH groups at 5 and 6 and at 6 and 7 positions, as well as nonoxygenated systems, has been evaluated for central dopaminergic effects. Stereotypical behavioral effects (sniffing, compulsive gnawing, and hyperactivity) produced by direct intracerebral administration of some of the agents were shown to differ strikingly from responses resulting from peripheral administration. The centrally mediated responses of hyperactivity and sterotypical gnawing-biti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(37 citation statements)
references
References 13 publications
(20 reference statements)
1
36
0
Order By: Relevance
“…The weaker action of apomorphine intracerebrally suggests that the drug may have a more restricted access to appropriate receptors when injected by this route. As in other reports, (Cannon, Lee, Goldman, Costall & Naylor, 1977;Makanjuola, Dow & Ashcroft, 1980) we found that dopamine receptor agonists required a considerable time, 1-2 h, to reach peak effect following intracerebral injection, suggesting a slow rate of diffusion to active sites. In this context, apomorphine may diffuse less readily than other agonists following localised injection into brain tissue.…”
Section: Discussionsupporting
confidence: 89%
“…The weaker action of apomorphine intracerebrally suggests that the drug may have a more restricted access to appropriate receptors when injected by this route. As in other reports, (Cannon, Lee, Goldman, Costall & Naylor, 1977;Makanjuola, Dow & Ashcroft, 1980) we found that dopamine receptor agonists required a considerable time, 1-2 h, to reach peak effect following intracerebral injection, suggesting a slow rate of diffusion to active sites. In this context, apomorphine may diffuse less readily than other agonists following localised injection into brain tissue.…”
Section: Discussionsupporting
confidence: 89%
“…Cannon et al [9] described the second method for the preparation of 2 starting from ethyl 3-(3,4-dimethoxyphenyl)propanoate. Horn et al [10] developed a procedure for the synthesis of 2 starting from (3,4-dimethoxyphenyl)acetic acid.…”
mentioning
confidence: 99%
“…Racemic 5,6-ADTN has been synthesized in many laboratories (McDermed et al, 1975;Horn et al, 1978;Sprenger, Cannon, Barman & Burkman, 1969;Mitsuhashi, Adachi, Shimizu, Nomura & Shiotani, 1972;Cannon & Costal, 1977), but none of the synthetic routes seem to be suitable on a multigram scale owing to their overall low yield. To overcome this difficulty, we studied an alternative route which does not require any purification by chromatography and which gives an improved overall yield.…”
Section: Commentmentioning
confidence: 99%